자동차 시동용 LFP 배터리 팩의 혹한기 시동성 향상을 위한 열선 시스템 적용에 따른 열 유동 해석 - 우영한(Younghan Woo); 강석원(Seokwon Kang); 이준숭(Junsoong Lee); 박문식(Moonsic Park); 김성진(Sungjin Kim); 성동길(Donggil Sung); 주성욱(Sungwook Joo) (한국생산제조학회지, 2021)
A numerical simulation for evaluating thermal performance was performed to determine the possibility of replacing existing lead-acid 12 V batteries with lithium-ion batteries. In batteries used for starting vehicles, low-temperature (≤–20℃) starting performance and lifespan decrease significantly. Therefore, a lithium iron phosphate (LFP) battery system with a relatively high energy density at low temperatures was studied. A system for self-energy heating was designed to improve operability under cold-weather conditions. In particular, the battery pack case, battery cell array, and heating system of the proposed system were designed to be compatible. Furthermore, a thermal performance simulation was performed using computational fluid dynamics and heat transfer techniques based on the estimated thermal properties of each component. The results showed that the self-heating LFP battery pack system reached its startable temperature (–3℃) after 75 s when 249 W of power was applied in a low-temperature (–20℃) environment. KCI Citation Count: 0